A preparation method and application of modified spherical nano-aluminum oxide
Spherical nano aluminum trioxide was prepared by ultrasonic assisted hydrothermal method, and graft polymerization was carried out on its surface, introducing hydrophilic polymer molecular chains, solving the lack of agglomeration and adsorption performance of nano aluminum trioxide in adsorption materials. The problem has significantly improved its dispersion and adsorption properties in water, and expanded its application in water pollution control.
Patent Information
- Application Number
- CN202410345977.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-03-26
AI Technical Summary
Nanoaluminum trioxide is prone to agglomeration in adsorption materials and has poor adsorption performance, especially the adsorption performance of pollutants such as phenols and dyes, making it difficult to effectively treat industrial wastewater and medical wastewater.
Spherical nano aluminum trioxide was prepared by ultrasonic assisted hydrothermal method, and graft polymerization was carried out on its surface by glycidyl hydroxypropanesulfonate tyrosine to introduce hydrophilic polymers of sulfonic acid, carboxyl and hydroxyl groups. Molecular chains improve their dispersion and adsorption properties.
The dispersion of modified spherical nano aluminum oxide in water and the adsorption performance of pollutants such as phenols and dyes has been significantly improved, and its application in water pollution control has been expanded.
Smart Images

Figure CN118184910B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum oxide, in particular to a preparation method of modified spherical nano aluminum oxide and application thereof. Background Art
[0002] Nano-aluminum oxide is a common inorganic oxide, which is cheap and easy to obtain, and has a simple preparation method. It is widely used in flame retardants, adsorbent materials, ceramic composites, and polymer composites. However, nano-aluminum oxide is easy to agglomerate and has poor adsorption performance, which is not conducive to its practical application in adsorption materials and the like. Therefore, it is necessary to modify the surface of nano-aluminum oxide to improve its dispersion and adsorption properties. Patent CN107081132B discloses a method for preparing an amine-functionalized γ-aluminum oxide film, which uses an organic amine solution to impregnate the γ-Al2O3 film to obtain an amine-functionalized γ-Al2O3 film, which exhibits excellent selective adsorption capacity for metal ions such as Cr, Cd, and Cu. However, the amine-functionalized γ-Al2O3 film does not exhibit good adsorption performance for pollutants such as phenols and dyes.
[0003] Industrial sewage, medical wastewater, printing and dyeing wastewater, etc. contain a large amount of organic pollutants, such as phenols, dyes such as methylene blue, organic solvents such as ethylene glycol, which are highly toxic and have great harm to the water environment and people's health and safety. Therefore, the treatment of wastewater containing phenols, dyes, etc. is imminent. The present invention aims to prepare polymer-modified spherical nano-aluminum trioxide to improve its adsorption performance for pollutants such as phenols and dyes. Summary of the invention
[0004] The technical problem solved by the invention is to provide a modified spherical nano aluminum oxide for water pollution control.
[0005] The technical solution is: a method for preparing modified spherical nano-aluminum oxide:
[0006] (1) Add ethanol, spherical nano-aluminum oxide and γ-methacryloxypropyltrimethoxysilane to a reaction bottle, place it in an ultrasonic instrument for ultrasonic dispersion for 30-60 minutes, then heat treat the solution in a heating box at 100-130°C for 2-6 hours, wash with ethanol, dry, and finally calcine in a resistance furnace at 500-550°C for 20-30 minutes to obtain vinyl spherical nano-aluminum oxide.
[0007] (2) Add distilled water and vinyl spherical nano-alumina into the reaction bottle, disperse by ultrasonic, then add acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and initiator, react at 65-75°C for 6-18h, filter, wash with water and dry to obtain modified spherical nano-alumina.
[0008] Furthermore, the mass of γ-methacryloxypropyltrimethoxysilane is 1-4% of the mass of spherical nano-aluminum oxide.
[0009] Furthermore, the masses of acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and the initiator are 200-800% and 1.2-5% of the mass of the vinyl spherical nano-aluminum oxide, respectively.
[0010] Furthermore, the initiator is any one of potassium persulfate and ammonium persulfate.
[0011] Furthermore, the preparation method of spherical nano-aluminum oxide is as follows: add hydrochloric acid solution to a reaction bottle, drop an aqueous solution containing aluminum chloride, then place it in an ultrasonic instrument, ultrasonicate it at a frequency of 20-25KHz, and drop an ammonia solution at the same time, adjust the solution pH to 8-9, react for 10-15 minutes, centrifuge after the reaction, wash with water and ethanol, and dry to obtain spherical nano-aluminum oxide.
[0012] Further, the preparation method of glycidyl hydroxypropanesulfonate tyrosine acrylate is:
[0013] (1) Add tetrahydrofuran, glycidyl methacrylate and D,L-tyrosine to a reaction flask, react at 30-50°C for 4-8 hours, concentrate the solution, and recrystallize the product from ethyl acetate to obtain glycidyl methacrylate tyrosine.
[0014] (2) Add acetonitrile, glycidyl methacrylate tyrosine, sodium 3-chloro-2-hydroxypropyl sulfonate and potassium carbonate to a reaction flask, react at 70-80° C. for 12-24 hours, concentrate the solution after the reaction, add it to distilled water, add hydrochloric acid solution dropwise to precipitate, filter the solution, wash with water and acetone, and dry to obtain glycidyl methacrylate tyrosine sulfonate.
[0015] Furthermore, the mass of D,L-tyrosine in (2) is 70-75% of the mass of glycidyl methacrylate.
[0016] Furthermore, the mass of sodium 3-chloro-2-hydroxypropyl sulfonate and potassium carbonate in (2) is 65-78% and 90-120% of the mass of glycidyl tyrosine methacrylate, respectively.
[0017] Furthermore, hydrochloric acid solution is added dropwise in (2) to adjust the pH to 4-5.
[0018] Furthermore, the modified spherical nano-aluminum oxide is used in water pollution control.
[0019] The technical effect of the present invention is as follows: the present invention prepares spherical nano aluminum oxide with uniform particle size and high specific surface area by ultrasonic-assisted hydrothermal method. Further, acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine is used to undergo graft polymerization reaction on the surface of vinyl vinyl spherical nano aluminum oxide, and hydrophilic polymer molecular chains of sulfonic acid, carboxyl and hydroxyl are grafted on the surface of nano aluminum oxide, which significantly improves the dispersibility of the modified spherical nano aluminum oxide in water, and is conducive to improving its adsorption performance.
[0020] The polymer molecular chain grafted with the spherical nano-aluminum oxide of the present invention contains phenolic hydroxyl groups, which can interact with phenol by π-π bonds. Meanwhile, the hydroxyl groups, carboxyl groups and sulfonic acid groups contained in the polymer chain can interact with phenol by hydrogen bonds, thereby significantly improving the adsorption performance and removal rate of the modified spherical nano-aluminum oxide on phenol.
[0021] The invention grafts hydrophilic polymer molecular chains of sulfonic acid, carboxyl and hydroxyl groups on the surface of nano aluminum oxide, significantly improving the dispersibility of the modified spherical nano aluminum oxide in water, which is beneficial to improving its adsorption performance. The hydroxyl, carboxyl and sulfonic acid groups can be ionized to form anions, which can form electrostatic interactions with cationic dyes such as methylene blue, thereby significantly improving the adsorption performance and removal rate of methylene blue by the modified spherical nano aluminum oxide. The practical application of aluminum oxide in water pollution control such as phenol-containing wastewater and printing and dyeing wastewater is expanded. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of spherical nano-aluminum oxide. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] (1) Add 20 mL of hydrochloric acid solution (pH 5) to the reaction bottle, add 5 mL of an aqueous solution containing 1 g of aluminum trichloride, and then place it in an ultrasonic instrument and ultrasonicate it at a frequency of 20 kHz. At the same time, add an ammonia solution to adjust the solution pH to 8. React for 15 minutes. After the reaction, centrifuge, wash with water and ethanol, and dry to obtain spherical nano-aluminum trioxide.
[0026] (2) Add 30 mL of ethanol, 3 g of spherical nano-aluminum oxide, and 0.03 g of γ-methacryloxypropyltrimethoxysilane into a reaction bottle, place it in an ultrasonicator for ultrasonic dispersion for 30 min, then heat treat the solution in a heating box at 130 ° C for 2 h, wash with ethanol, dry, and finally calcine in a resistance furnace at 550 ° C for 20 min to obtain vinyl spherical nano-aluminum oxide.
[0027] (3) Add 60 mL of tetrahydrofuran, 6 g of glycidyl methacrylate, and 4.2 g of D,L-tyrosine to the reaction flask, react at 40°C for 8 h, concentrate the solution, and recrystallize the product with ethyl acetate to obtain glycidyl methacrylate tyrosine. The reaction formula is as follows:
[0028] .
[0029] (4) Add 80 mL of acetonitrile, 8 g of methacrylate glycidyl tyrosine, 5.2 g of sodium 3-chloro-2-hydroxypropyl sulfonate and 9.6 g of potassium carbonate to a reaction flask, react at 70°C for 18 h, concentrate the solution after the reaction, add it to distilled water, add hydrochloric acid solution dropwise to adjust the pH to 5, precipitate the precipitate, filter the solution, wash with water and acetone, and dry to obtain methacrylate glycidyl hydroxypropyl sulfonate tyrosine. The reaction formula is as follows:
[0030] .
[0031] (5) Add 50 mL of distilled water and 3 g of vinyl spherical nano-alumina into the reaction bottle, disperse by ultrasonic, then add 6 g of acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and 0.036 g of initiator potassium persulfate, react at 65 ° C for 12 h, filter, wash with water and dry to obtain modified spherical nano-alumina.
[0032] Example 2
[0033] (1) Add 20 mL of hydrochloric acid solution (pH 5) to the reaction bottle, add 5 mL of an aqueous solution containing 1 g of aluminum chloride, and then place it in an ultrasonic instrument and ultrasonicate it at a frequency of 25 kHz. At the same time, add an ammonia solution and adjust the pH of the solution to 8. React for 10 minutes. After the reaction, centrifuge, wash with water and ethanol, and dry to obtain spherical nano-aluminum oxide.
[0034] (2) Add 40 mL of ethanol, 3 g of spherical nano-aluminum oxide, and 0.08 g of γ-methacryloxypropyltrimethoxysilane into a reaction bottle, place it in an ultrasonicator for ultrasonic dispersion for 60 min, then heat treat the solution at 100 °C in a heating box for 6 h, wash with ethanol, dry, and finally calcine at 550 °C in a resistance furnace for 20 min to obtain vinyl spherical nano-aluminum oxide.
[0035] (3) Add 100 mL of tetrahydrofuran, 6 g of glycidyl methacrylate, and 4.5 g of D,L-tyrosine to a reaction flask, react at 50°C for 4 h, concentrate the solution, and recrystallize the product from ethyl acetate to obtain glycidyl methacrylate tyrosine.
[0036] (4) Add 100 mL of acetonitrile, 8 g of methyl methacrylate glycidyl tyrosine, 6.24 g of sodium 3-chloro-2-hydroxypropyl sulfonate and 9.6 g of potassium carbonate to a reaction bottle, and react at 70° C. for 12 h. After the reaction, concentrate the solution and add it to distilled water. Add hydrochloric acid solution dropwise to adjust the pH to 4 to precipitate the precipitate. Filter the solution, wash with water and acetone, and dry to obtain glycidyl methacrylate glycidyl hydroxypropyl sulfonate tyrosine.
[0037] (5) Add 80 mL of distilled water and 3 g of vinyl spherical nano-alumina into a reaction bottle, disperse by ultrasonication, then add 18 g of acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and 0.092 g of initiator ammonium persulfate, react at 65 °C for 18 h, filter, wash with water and dry to obtain modified spherical nano-alumina.
[0038] Example 3
[0039] (1) Add 20 mL of hydrochloric acid solution (pH 5) to the reaction bottle, add 5 mL of an aqueous solution containing 1 g of aluminum trichloride, and then place it in an ultrasonic instrument and ultrasonicate it at a frequency of 25 kHz. At the same time, add an ammonia solution and adjust the pH of the solution to 9. React for 10 minutes. After the reaction, centrifuge, wash with water and ethanol, and dry to obtain spherical nano-aluminum trioxide.
[0040] (2) Add 40 mL of ethanol, 3 g of spherical nano-aluminum oxide, and 0.12 g of γ-methacryloxypropyltrimethoxysilane into a reaction bottle, place it in an ultrasonicator for ultrasonic dispersion for 60 min, then heat treat the solution at 120 ° C in a heating box for 2 h, wash with ethanol, dry, and finally calcine at 500 ° C in a resistance furnace for 30 min to obtain vinyl spherical nano-aluminum oxide.
[0041] (3) Add 100 mL of tetrahydrofuran, 6 g of glycidyl methacrylate, and 4.5 g of D,L-tyrosine to a reaction flask, react at 30°C for 8 h, concentrate the solution, and recrystallize the product from ethyl acetate to obtain glycidyl methacrylate tyrosine.
[0042] (4) Add 100 mL of acetonitrile, 8 g of methyl methacrylate glycidyl tyrosine, 6.24 g of sodium 3-chloro-2-hydroxypropyl sulfonate and 7.2 g of potassium carbonate to a reaction bottle, and react at 80° C. for 24 h. After the reaction, concentrate the solution and add it to distilled water. Add hydrochloric acid solution dropwise to adjust the pH to 4 to precipitate the precipitate. Filter the solution, wash with water and acetone, and dry to obtain glycidyl methacrylate glycidyl hydroxypropyl sulfonate tyrosine.
[0043] (5) Add 120 mL of distilled water and 3 g of vinyl spherical nano-alumina into a reaction bottle, disperse by ultrasonication, then add 24 g of acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and 0.15 g of initiator potassium persulfate, react at 75 °C for 6 h, filter, wash with water and dry to obtain modified spherical nano-alumina.
[0044] Comparative Example 1 is spherical nano-aluminum oxide (prepared in the same manner as in Example 1).
[0045] Comparative Example 2 is vinyl spherical nano-aluminum oxide (prepared in the same manner as in Example 1).
[0046] Comparative Example 3
[0047] (1) Add 60 mL of ethanol, 6 g of glycidyl methacrylate, and 4.2 g of D,L-tyrosine to a reaction flask, react at 40°C for 8 h, concentrate the solution, and recrystallize the product from ethyl acetate to obtain glycidyl methacrylate tyrosine. The structural formula is .
[0048] (2) Add 50 mL of distilled water and 3 g of vinyl spherical nano-alumina (prepared in the same manner as in Example 1) into a reaction flask, disperse by ultrasonication, then add 6 g of methacrylate glycidyl tyrosine and 0.036 g of initiator potassium persulfate, react at 65 °C for 12 h, filter, wash with water and dry to obtain modified spherical nano-alumina.
[0049] The modified spherical nano-aluminum oxide (1 g) prepared in the examples and comparative examples was added into 100 mL of distilled water, stirred evenly and allowed to stand for 24 hours, and the state of the solution was observed.
[0050]
[0051] In Examples 1-3 of the present invention, acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine is used to undergo a graft polymerization reaction on the surface of vinyl vinyl spherical nano-aluminum oxide, and hydrophilic polymer molecular chains of sulfonic acid, carboxyl and hydroxyl groups are grafted on the surface of the nano-aluminum oxide, which significantly improves the dispersibility of the modified spherical nano-aluminum oxide in water, and its aqueous solution is uniform, stable and free of precipitation.
[0052] Comparative Example 1 is spherical nano-aluminum oxide, which has poor dispersibility in water, has aggregated, and has a large amount of precipitation.
[0053] Comparative Example 2 is vinyl spherical nano aluminum oxide. The surface of the spherical nano aluminum oxide is modified by using γ-methacryloxypropyltrimethoxysilane; however, γ-methacryloxypropyltrimethoxysilane is hydrophobic, which results in poor dispersibility of the vinyl spherical nano aluminum oxide in water.
[0054] In Comparative Example 3, methacrylate glycidyl tyrosine is used to undergo a graft polymerization reaction on the surface of vinyl vinyl spherical nano-alumina, and hydrophilic polymer molecular chains of amino, carboxyl and hydroxyl groups are grafted on the surface of the nano-alumina. The dispersion in water is also very good, but it does not contain sulfonic acid groups, resulting in lower dispersibility than that of the various embodiments.
[0055] Prepare 100mL of 50mg / L phenol aqueous solution, add different masses (m) of modified spherical nano-alumina, adsorb at room temperature for 4h, take the upper clear liquid after adsorption, measure the phenol concentration by UV spectrophotometry, and calculate the removal rate Q. Removal rate Q = (C0-C) ÷ C0 × 100%. The test results are shown in the following table.
[0056]
[0057] In Example 1-3, acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine is used to carry out graft polymerization reaction on the surface of vinyl vinyl spherical nano aluminum oxide, and hydrophilic polymer molecular chains of sulfonic acid, carboxyl and hydroxyl are grafted on the surface of nano aluminum oxide, which significantly improves the dispersibility of the modified spherical nano aluminum oxide in water, and is conducive to improving its adsorption performance. In addition, the grafted polymer molecular chain contains phenolic hydroxyl groups, which can interact with phenol by π-π bonds, and the hydroxyl, carboxyl and sulfonic acid groups contained in the grafted polymer molecular chain can interact with phenol by hydrogen bonds, which significantly improves the adsorption performance and removal rate of the modified spherical nano aluminum oxide to phenol.
[0058] Comparative Example 1 is spherical nano-aluminum oxide, and Comparative Example 2 is vinyl spherical nano-aluminum oxide. The interaction force with phenol is very low, and the adsorption performance is very poor.
[0059] Comparative Example 3 uses methacrylate glycidyl tyrosine to undergo graft polymerization reaction on the surface of vinyl vinyl spherical nano-alumina, which contains functional groups such as phenolic hydroxyl and carboxyl, and has good interaction and adsorption properties for phenol.
[0060] Prepare 100mL of 50mg / L methylene blue aqueous solution, add different masses (m) of modified spherical nano-alumina, adsorb at room temperature for 4h, take the upper clear liquid after adsorption, determine the phenol concentration by ultraviolet spectrophotometry, and calculate the removal rate Q. Removal rate Q = (C0-C) ÷ C0 × 100%. The test results are shown in the following table.
[0061]
[0062] In Example 1-3, hydrophilic polymer molecular chains of sulfonic acid, carboxyl and hydroxyl groups are grafted on the surface of nano-aluminum trioxide, which significantly improves the dispersibility of the modified spherical nano-aluminum trioxide in water and is conducive to improving its adsorption performance. Its hydroxyl, carboxyl and sulfonic acid groups can be ionized to form anions, which can form electrostatic interactions with cationic dyes such as methylene blue, thereby significantly improving the adsorption performance and removal rate of methylene blue by the modified spherical nano-aluminum trioxide.
[0063] In Comparative Example 3, the polymer grafted on the surface of the spherical nano-aluminum oxide does not contain sulfonic acid groups, and its electrostatic interaction with methylene blue is weaker than that of the examples, resulting in a lower removal rate than that of the examples.
[0064] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing modified spherical nano-aluminum oxide, characterized in that: The preparation method comprises the following steps: (1) Add ethanol, spherical nano-aluminum trioxide and γ-methacryloxypropyltrimethoxysilane to a reaction bottle, place it in an ultrasonic instrument for ultrasonic dispersion for 30-60 minutes, then heat treat the solution in a heating box at 100-130°C for 2-6 hours, wash, dry, and finally calcine in a resistance furnace at 500-550°C for 20-30 minutes to obtain vinyl spherical nano-aluminum trioxide; (2) Add distilled water and vinyl spherical nano-alumina into the reaction bottle, disperse by ultrasonic, then add acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and initiator, react at 65-75°C for 6-18h, filter, wash and dry to obtain modified spherical nano-alumina; The preparation method of the glycidyl hydroxypropanesulfonyl tyrosine acrylate is as follows: (1) Add tetrahydrofuran, glycidyl methacrylate and D,L-tyrosine to a reaction flask, react at 30-50°C for 4-8 hours, concentrate the solution, and recrystallize the product from ethyl acetate to obtain glycidyl methacrylate tyrosine; (2) Add acetonitrile, glycidyl methacrylate tyrosine, sodium 3-chloro-2-hydroxypropyl sulfonate and potassium carbonate to a reaction flask, react at 70-80° C. for 12-24 hours, concentrate the solution after the reaction, add it to distilled water, add hydrochloric acid solution dropwise to precipitate, filter the solution, wash, and dry to obtain glycidyl methacrylate tyrosine sulfonate.
2. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: The mass of the γ-methacryloxypropyltrimethoxysilane is 1-4% of the mass of the spherical nano-aluminum oxide.
3. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: The masses of the acrylic acid glycidyl hydroxypropanesulfonic acid tyrosine and the initiator are 200-800% and 1.2-5% of the mass of the vinyl spherical nano-aluminum oxide, respectively.
4. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: The initiator is any one of potassium persulfate and ammonium persulfate.
5. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: The preparation method of the spherical nano-aluminum trioxide is as follows: adding hydrochloric acid solution into a reaction bottle, dripping an aqueous solution containing aluminum chloride, then placing the reaction bottle in an ultrasonic instrument, ultrasonically treating the reaction bottle at a frequency of 20-25 kHz, dripping an ammonia solution, adjusting the pH value of the reaction bottle to 8-9, reacting the reaction bottle for 10-15 minutes, centrifuging the reaction bottle after the reaction, washing the reaction bottle, and drying the reaction bottle to obtain the spherical nano-aluminum trioxide.
6. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: In the method for preparing glycidyl hydroxypropanesulfonate tyrosine acrylate, the mass of D,L-tyrosine in (1) is 70-75% of the mass of glycidyl methacrylate.
7. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: In the method for preparing glycidyl hydroxypropyl methacrylate tyrosine, the masses of sodium 3-chloro-2-hydroxypropyl sulfonate and potassium carbonate in (2) are 65-78% and 90-120% of the mass of glycidyl methacrylate tyrosine, respectively.
8. The method for preparing modified spherical nano-aluminum oxide according to claim 1, characterized in that: In the method for preparing glycidyl hydroxypropanesulfonic acid tyrosine acrylate, hydrochloric acid solution is added dropwise in (2) to adjust the pH to 4-5.
9. Use of the modified spherical nano-aluminum oxide obtained by the preparation method according to any one of claims 1 to 8 in water pollution control.
Citation Information
Patent Citations
A method for preparing amino-functionalized γ-alumina thin films
CN107081132B
Surface fluorine-containing nanosphere capable of crosslinking as well as preparation method and application thereof
CN102432781A
Method for preparing macromolecular adsorbents with large specific surface area
CN107955093A